Optimization of ignition zone of advanced fast reactor, working in nuclear burning wave mode - Fomin, S.P.; Kirdin, A.I.; Malovytsia, M.S.; Pilipenko, V.V.; Shul’ga, N.F. (Вопросы атомной науки и техники, 2019)
This article deals with the problem of optimizing composition and structure of the ignition zone of the fast reactor operating in the self-sustaining mode of nuclear burning wave with the purpose of its smooth start-up and reducing ﬁssile material amount in initial assembly. The cylindrical homogeneous reactor with the ignition zone placed in the center or near the cylinder end is considered. The analysis has been performed basing on solving the non-stationary neutron diﬀusion equation together with the fuel burn-up equations and the equations of nuclear kinetics for precursor nuclei of delayed neutrons, with using the radial buckling approximation. An optimized structure of the ignition zone has been proposed, which ensures a smooth transition of the reactor to the self-sustaining nuclear burning wave mode, avoiding an excessive energy release, which is observed when using a simpliﬁed scheme of ignition zone. Comparison of the startup variants with the ignition zone at the cylinder end and at its center shows the beneﬁts of the second one. Вивчається питання оптимізації складу та структури зони запалу швидкогоого реактора, працюючого в режимі самопідтримки хвилі ядерного горіння, з метою його плавного запуску та економії материалів, які діляться на цоому етапі. Розглядався гомогенний реактор ціліндричної форми з центральним або торцевим розміщенням зони запалу. Аналіз проводився на основі числового рішения нестаціонарного рівняння диффузії нейтронів разом з рівняннями вигорання і рівняннями кінетики ядер попередників запізнюющихся нейтронів. Задача рішалася з використанням наближення геометричного фактора ("баклінга"). Запропонована оптимізована структура зони запалу, яка забезпечує плавний вихід ректора на стаціонарний режим хвилі ядерного горіння, яка самопідтримується, уникаючи значного росту енерговиділення, яке спостерігається при використанні спрощеної схеми зони запалу. Проведено порівняння кількості материалу, якой ділеться, необхідного для запуску реактора, при двох варіантах розположення зони запалу: торцевої та центральної. Изучается вопрос оптимизации состава и структуры зоны запала быстрого реактора, работающего в самоподдерживающемся режиме волны ядерного горения, с целью его плавного запуска и экономии делящихся материалов на этом этапе. Рассматривался гомогенный реактор цилиндрической формы с центральным либо торцевым расположением зоной запала. Анализ проводился на основе численного решения нестационарного уравнения диффузии нейтронов вместе с уравнениями выгорания и уравнениями кинетики ядер предшественников запаздывающих нейтронов. Задача решалась с использованием приближения геометрического фактора ("баклинга"). Предложена оптимизированная структура зоны запала, обеспечивающая плавный выход реактора на стационарный самоподдерживающийся режим волны ядерного горения, избегая значительного роста энерговыделения, который наблюдается при использовании упрощенной схемы зоны запала. Проведено сравнение количества делящегося материала, необходимого для запуска реактора, при двух вариантах расположения зоны запала: торцевой и центральной.